A Comparative Study on the Divalent Metal Ions Sensing Performance of 2-D CuS and SnS2 Nanostructures - Sahin, Ayse Nur; Altindal, Ahmet; Guven Ozdemir, Zeynep (SPRINGER, 2026)
This study presents comparative investigation of the QCM-based sensing performance of hydrothermally synthesized 2-D CuS and SnS2 nanostructures toward divalent metal ions (Co2+, Ni2+, Zn2+, Cu2+, and Mg2+) in aqueous media, offering new insights into their sensing behavior. Unlike previous studies mainly focused on single-material adsorption or electrochemical sensing approaches, the present work systematically compares the QCM sensing behavior of CuS and SnS2 nanosheets toward multiple divalent metal ions under identical aqueous sensing conditions and provides a physicochemical interpretation of the adsorption-driven sensing mechanism. After the structural and morphological characterizations by XRD, FE-SEM, and TEM techniques, thin film of the sensing unit was deposited on Quartz Crystal Microbalance (QCM) transducers. XRD results showed that CuS in covellite phase and SnS2 in Berndtite - 2T phase were successfully synthesized. FE-SEM and TEM results revealed that CuS nanostructures have an average thickness of approximately 31 nm and lateral dimensions of around 146 nm, while SnS2 exhibits a thickness of about 38 nm with lateral dimensions of approximately 140 nm. QCM results showed that the maximum sensitivity was observed for Mg2+ ions with CuS- and SnS2-based sensors. On the other hand, limit of detection (LoD) calculations showed that CuS-based sensors seem to be more suitable for detecting low concentrations of Mg2+ ions, with the LoD value of 0.72 ppm, while SnS2-based sensors seem to be more suitable for detecting very low concentrations of Co2+ ions. In addition, UV-Vis absorption analysis revealed noticeable spectral shifts after ion adsorption, indicating changes in the electronic environment of S2- active sites and supporting the occurrence of ion-surface interactions. The adsorption isotherms of the DMIs from aqueous solutions onto CuS and SnS2 were modelled using Langmuir, Freundlich, Temkin, and Jovanovic isotherm models. Regression analysis showed that the number of sulfur atoms and the acidity of the analyte ions have a strong effect on the DMIs adsorption isotherm.
Keywords: Metal chalcogenide nanostructures; Divalent metal ion (DMI) detection; Quartz crystal microbalance (QCM); Adsorption isotherms; Selectivity and sensitivity in aqueous media; FLUORESCENT CHEMOSENSOR; SELECTIVE DETECTION; AQUEOUS-SOLUTIONS; COPPER; CU2+; CO2+; NANOCOMPOSITE; SORPTION; REMOVAL; NICKEL; Polymer Science